What is the optimal duration for vigabatrin monotherapy in patients with infantile spasms: 6 months or longer?. (October 2021) - Desnous, Béatrice; Lenoir, Marien; Bitton, Jonathan Y.; Arbour, Mélina; Villeneuve, Nathalie; Whiting, Sharon; Mohammed, Ismail; Wirrell, Elaine C.; Bello-Espinosa, Luis; Ronen, Gabriel M; Lortie, Anne; Birca, Ala
Abstract: Vigabatrin (VGB) is approved as monotherapy for pediatric patients with Infantile Spasms (IS). Duration of VGB use should be limited because of the risk of retinal and neurotoxicity, but the optimal length of treatment is unknown. Our study aimed to determine the risk of spasms relapse after 6 months of VGB as first-line therapy in IS patients deemed VGB good responders. The participants were 44 infants with IS who demonstrated both absence of clinical spasms and hypsarrhythmia four weeks after starting VGB, obtained from two cohorts: 29 patients from a multicenter prospective cohort and 15 patients from a retrospective single-center cohort. We divided them post hoc into two groups according to the duration of VGB treatment: 6-month group (n=34) and >6-month group (n=10) and compared outcome between the two groups. No patient in either group had a relapse of spasms. For patients with non-identified etiology (NIE) in the 6 months treatment group, no other seizure types were observed. Late epilepsy, in the form of focal seizures, emerged in only 5/37 patients (3/30 in the 6-month treatment group; 2/7 in the extended treatment group); all within the first 6-9 months after VGB initiation. Our study provides substantial evidence that a shortened VGB course of 6 months could be sufficient to treat and prevent relapse of spasms in children with IS, particularly those with NIE.